Spatial distribution of heathlands in the north-western part of Poland (Pomerania District) - Kunz, Mieczysław; Nienartowicz, Andrzej (Ecological Questions, 2010)
Spatial distribution of heathlands in Pomerania (the north-western part of Poland) was described based on the results of questionnaires sent out to the registered offices of all forest divisions (96), national (4) and landscape (15) parks of this area. According to the inventory, heathlands occur in 28 forest divisions and 3 national and landscape parks. The frequency of occurrence and the area covered by heathlands were determined. All the data were compiled in the form of a spatial database with the use of Geographic Information Systems. The paper also contains the geographical distribution of heath habitats in the area of Pomerania according to particular syntaxa. Additionally, the content of the database CORINE Land Cover was analysed at the third level for the area of Pomerania, completed for the years of 2000 and 2006. The area and the number of patches were described according to three land cover categories: heaths (code 322), conflagration sites (code 334) and peat bogs (code 412).